Competitive Intelligence and Resilience of Small Medium Enterprises (SMEs) in Developing Economies - Ngboawaji Daniel Nte; Nduka Kenneth Omede (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Small and Medium Enterprises SMEs hold the key to economic progress and development in developing economies including Nigeria. This study therefore examined the effect of competitive intelligence on the survival of SMEs in Benin City, Edo State, Nigeria. To achieve these objectives three hypotheses were formulated to establish whether or not there is a relationship existing between the two intervening variable i.e. competitive intelligence and the survival of SMEs in Benin City, Edo State and by extension Nigeria. Survey research design was adopted, while data were obtained from structured questionnaire and analyzed using Pearson’s product-moment coefficient of correlation. From the analysis, the results indicated that there is an existing relationship between the variables. Based on the findings it was concluded that for SMEs to survive and expand its market frontiers in the face of the escalating competition in the business environment, there is the need to take a holistic view of their strategies and offer innovative products that can provide customers with valued and satisfying benefits better than the ones offered by competitors and engaging in superior marketing strategies to enhance performance and productivity. The study recommended among others that SMEs should identify and prune down unwarranted business expenses without necessarily impacting negatively on the operations of the firm. Keywords: Innovative Products, Performance, Productivity, Satisfying Benefits, SMEs, Survival.